The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.5230/jgc.2016.16.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Clinicopathological Significance of Transducer-Like Enhancer of Split 1 Expression in Gastric Cancer

Abstract: PurposeTransducer-like enhancer of split 1 (TLE1) is a member of the Groucho/TLE family of transcriptional co-repressors that regulate the transcriptional activity of numerous genes. TLE1 is involved in the tumorigenesis of various tumors. We investigated the prognostic significance of TLE1 expression and its association with clinicopathological parameters in gastric cancer (GC) patients.Materials and MethodsImmunohistochemical analysis of six tissue microarrays was performed to examine TLE1 expression using 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
3
10
0
Order By: Relevance
“…This suggests an oncogenic effect of TLE1 in breast carcinogenesis. These findings are similar to those reported previously in gastric, breast, and lung cancer [161718]. …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This suggests an oncogenic effect of TLE1 in breast carcinogenesis. These findings are similar to those reported previously in gastric, breast, and lung cancer [161718]. …”
Section: Discussionsupporting
confidence: 93%
“…Normal gastric mucosa has no TLE1 expression. We suggested that TLE1 had an oncogenic effect in gastric cancer [16]. In a study analyzing breast tissue by IHC, TLE1 was significantly overexpressed in IBC tissues (67.4%) compared to normal breast tissue and DCIS samples [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations